2018
DOI: 10.1002/jso.24946
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of differentiation at the invasive front of biliary tract cancer

Abstract: Poor differentiation at the invasive front of tumor was associated with poor prognosis and early relapse in BTC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Several reports used immunohistochemistry by cytokeratin to easily identify TB at stroma [8,25]. Okubo et al [12] demonstrated the strong correlation between TB counts cytokeratinstained tissue and the H&E-stained tissue sections in In patients with neoadjuvant therapy, patients in high TB group had significantly poor survival as compared to patients in low TB group (p < 0.001 in DSS, p = 0.001 in RFS). Similarly, in patients without neoadjuvant therapy, patients in high TB group had significantly poor DSS and had a tendency with poor RFS, as compared to patients in low TB group (p = 0.004 in DSS, p = 0.127 in RFS).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several reports used immunohistochemistry by cytokeratin to easily identify TB at stroma [8,25]. Okubo et al [12] demonstrated the strong correlation between TB counts cytokeratinstained tissue and the H&E-stained tissue sections in In patients with neoadjuvant therapy, patients in high TB group had significantly poor survival as compared to patients in low TB group (p < 0.001 in DSS, p = 0.001 in RFS). Similarly, in patients without neoadjuvant therapy, patients in high TB group had significantly poor DSS and had a tendency with poor RFS, as compared to patients in low TB group (p = 0.004 in DSS, p = 0.127 in RFS).…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumor staging (pT) and regional lymph node metastasis (pN) were defined according to Union for International Cancer Control (UICC) 8th edition. TB was defined as an isolated cancer cell or clusters composed of fewer than 5 cancer cells at the site of tumor invasive front according to previous studies [10][11][12][13]. The invasive front was defined as the peripheral to whole primary tumor and in the most severe extended area of tumor to the surrounding tissue according to previous studies.…”
Section: Histology and Assessment Of Tumor Buddingmentioning
confidence: 99%
See 3 more Smart Citations